Introduction to management accounting - Horngren, Charles T.; Sundem, Gary L.; Stratton, William O. (New Delhi : Prentice-Hall of India, 2005)
Business
Keywords: Management accounting; Decision making; Planning; Capital budgeting; Product costing; Financial accounting